Papain-induced occupational rhinoconjunctivitis and asthma - A case report - Diana Tymoszuk; Marta Wiszniewska; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2016)
This report presents a case of occupational asthma, rhinitis and conjunctivitis to papain in a 50-year-old herbs and spices packer, with documented increased eosinophilia in induced sputum and in the nasal lavage fluids after a specific inhalation challenge test (SICT) and specific nasal challenge test (SNCT) with this enzyme. Immunoglobulin E-mediated (IgE) sensitization to papain was confirmed by positive results of a skin prick test with specific solution. Specific inhalation and nasal challenge tests demonstrated a direct and significant link between the exposure to this protease and the allergic response from the respiratory system. Additionally, the SNCT induced a severe reaction of the conjunctivae and a significant increase in the count of eosinophils in tears, despite the lack of direct contact of the allergen with the conjunctiva. Med Pr 2016;67(1):109-112